2009
DOI: 10.1080/17470210802661736
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning in face processing: Comparison facilitates face recognition

Abstract: Theoretical analyses of perceptual learning suggest that comparison between similar stimuli aids subsequent discrimination between them. The current studies examined whether the opportunity to compare a target face to other similar faces during a preexposure phase facilitated performance on a matching task. Performance was better when the target face had been presented in alternation with similar comparator faces than if that target had not been exposed before test. Exposure to the target face without comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 41 publications
(54 reference statements)
1
17
1
Order By: Relevance
“…This method aimed at training perceptual rather than memory processes and shares design elements with the Philadephia Face Similarity Test (Thomas, Lawler, Olson, & Aguirre, 2008) and another study of perceptual face training (Bate et al, 2015). The design reflected evidence from previous studies of perceptual learning of faces that suggested an advantage for simultaneous over sequential faces in discrimination tasks (Mundy, Honey, Downing, et al, 2009;Mundy, Honey, & Dwyer, 2007 and better perceptual learning for faces shown alongside similar rather than dissimilar faces (Dwyer & Vladeanu, 2009).…”
Section: Within-session Training Protocolmentioning
confidence: 99%
“…This method aimed at training perceptual rather than memory processes and shares design elements with the Philadephia Face Similarity Test (Thomas, Lawler, Olson, & Aguirre, 2008) and another study of perceptual face training (Bate et al, 2015). The design reflected evidence from previous studies of perceptual learning of faces that suggested an advantage for simultaneous over sequential faces in discrimination tasks (Mundy, Honey, Downing, et al, 2009;Mundy, Honey, & Dwyer, 2007 and better perceptual learning for faces shown alongside similar rather than dissimilar faces (Dwyer & Vladeanu, 2009).…”
Section: Within-session Training Protocolmentioning
confidence: 99%
“…One possibility that builds on exemplar views is that exposure to multiple speakers and linguistic contexts allows listeners to compare tokens to identify the similarities and differences across them and distinguish relevant from irrelevant variation, thus inducing category structure for accent-specific regularities (Gentner & Markman, 1994). The role of comparison has been examined in the categorization of novel objects (Gentner & Namy, 1999; Namy & Gentner, 2002), artistic styles (Kang & Pashler, 2012; Kornell & Bjork, 2008), and in face recognition (Clutterbuck & Johnston, 2005; Dwyer & Vladeanu, 2009). Kornell and Bjork (2008), for example, found that participants who saw paintings by different artists interleaved (spaced) during training better identified novel paintings by these artists than participants who saw the paintings blocked by artist (massed).…”
mentioning
confidence: 99%
“…One possibility that builds on exemplar views is that exposure to multiple speakers and linguistic contexts allows listeners to compare tokens to identify the similarities and differences across them and distinguish relevant from irrelevant variation, thus inducing category structure for accentspecific regularities (Gentner & Markman, 1994). The role of comparison has been examined in the categorization of novel objects (Gentner & Namy, 1999;Namy & Gentner, 2002), artistic styles (Kang & Pashler, 2012;Kornell & Bjork, 2008), and in face recognition (Clutterbuck & Johnston, 2005;Dwyer & Vladeanu, 2009). Kornell and Bjork (2008), for example, found that participants who saw paintings by different artists interleaved (spaced) during training better identified novel paintings by these artists than participants who saw the paintings blocked by artist (massed).…”
mentioning
confidence: 99%